Detecting soil salinity dynamics using Landsat 8 OLI/TIRS for sustainability land management in Pekalongan City, Central Java, Indonesia - Primadipta, Indira Wido; Saepuloh, Asep; Rachmayani, Rima; Ghazali, Mochamad Firman; Sahana, Muhammad Irham (Brawijaya University, 2025)
Soil salinization occurs when salts accumulate in the soil, damaging its structure and reducing fertility. Currently, about 20% of cultivated land is affected by salinity, and it is estimated that this figure could rise to 50% by 2050 if no preventive actions are taken. In Indonesia, saline soils are predominantly found in coastal regions, where seawater intrusion and tidal flooding are common. Pekalongan, a coastal city in Central Java with shallow groundwater, is particularly susceptible to salinization, as evidenced by increased groundwater salinity affecting a total area of 23.03 km². This study utilized Landsat 8 OLI/TIRS imagery to develop an enhanced soil salinity index for monitoring soil salinity dynamics in Pekalongan City from 2014 to 2024. Seven salinity indices were used to estimate soil salinity, and statistical analysis was conducted to examine the relationship between electrical conductivity (EC) and salinity indices derived from satellite imagery. A tailored soil salinity index, termed the modified Vegetation Soil Salinity Index (mVSSI), was developed, achieving a strong correlation with field data (R² = 0.81). The analysis showed notable changes in non-saline soil areas, which expanded from 3.32 km² in 2014 to 9.64 km² in 2024, likely due to efforts to mitigate seawater intrusion and tidal flooding. This study provides valuable insights into the dynamics of soil salinity and offers a reliable tool for monitoring and managing salinity in coastal regions, contributing to the broader goal of sustainable land management.